Femtosecond stimulated Raman spectroscopy. - Kukura, P; McCamant, D; Mathies, R (2007)
Femtosecond stimulated Raman spectroscopy (FSRS) is a new ultrafast spectroscopic technique that provides vibrational structural information with high temporal (50-fs) and spectral (10-cm(1)) resolution. As a result of these unique capabilities, FSRS studies of chemical and biochemical reaction dynamics are expected to grow rapidly, giving previously unattainable insight into the structural dynamics of reactively evolving systems with atomic spatial and femtosecond temporal resolution. This review discusses the experimental and theoretical concepts behind FSRS, with an emphasis on the origins of its unique temporal and spectral capabilities. We illustrate these capabilities with vibrational studies of ultrafast electronic dynamics, as well as the direct structural observation of nonstationary vibrational wave-packet motion in small molecules and in complex biochemical reaction dynamics.